Utawilaya rural school: A liberating Education in Puno - Peru 1902 - Ruelas Vargas, David (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2021)
This paper details the development of the Indigenous and rural School Utawilaya in the district Chucuito Platera, in the province of Puno- Peru in 1902. Because of the educational, economic, social and political exclusion of the rural population by the State, the teacher Manuel Zuniga Camacho founded the Indigenous and rural School with a pedagogical stance towards a liberating education. Zúñiga Camacho considered education as the only way of salvation from exclusion, exploitation and poverty; established by the oligarchs and political bosses. Peruvian historiography agrees that one of the strongest movements in the southern highlands in the early twentieth century was the struggle for education, which was considered as a privilege for the upper class or ruling elite (oligarchy and tyranny). This research work is based on unpublished historical documents, which contribute to the study of the history of Puno. Library research methods and techniques have been applied for reviewing primary and secondary sources leading to analysis and criticism. The marginalization of indigenous peoples is not a current phenomenon; it comes from two hundred years ago within the framework of the republican history. This exclusion underlies the perception (still current) of indigenous people as backward and ignorant, who therefore are not included in the development policies of the Peruvian State. For (Aliaga, 2015) the incidence of poverty, ``on grounds of´´ mother tongue, affects mainly the population with a native language: Quechua or Aymara. Thus, in 2013, poverty affected 35.9 % of the population. The Utawilaya school literacy program included groups of adults and children. The liberating education of Manuel Zúñiga Camacho highlights the following transcendental aspects: people´s liberation, community transformation, awareness, change of reality into an environment without discrimination, exploitation, humiliation and entitled to education.